1989
DOI: 10.1007/bf00006054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper and zinc on the growth and emergence of Epeorus latifolium (Ephemeroptera) in an indoor model stream

Abstract: Effects of Cu and Zn through food as well as through the water on the growth and emergence of the young larvae of Epeoms latgolium (Ephemeroptera), were investigated using an indoor model stream. The critical lowest concentrations of Cu which have significant effects on the growth of the larvae were between 10 and 15 pg 1-' Cu. Growth and emergence of the larvae fed on the algae (diatoms) which accumulated more than 1000 pg CU g-(dry wt.) were significantly impaired. Growth of the mayfly larvae exposed to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
0
21
2
Order By: Relevance
“…For instance, a 28-d exposure of Ephemerella sp. With Zn, the present results with the heptageniid mayfly Epeorus longimanus, with a larval EC50 estimate of 59 mg/L, were less sensitive than the EC50 estimate of 23 mg/L that we calculated from reported Epeorus latifolium larval survival following 35-d exposures in hardness 83 mg/L water [45]. Ephemerella was also the most sensitive taxa to Cd in the present results, with a 32-d EC50 of approximately 0.37 mg/L in water with a hardness of 17 mg/L (Table 1).…”
Section: Experimental Stream Results Relative To Standard Single-speccontrasting
confidence: 85%
“…For instance, a 28-d exposure of Ephemerella sp. With Zn, the present results with the heptageniid mayfly Epeorus longimanus, with a larval EC50 estimate of 59 mg/L, were less sensitive than the EC50 estimate of 23 mg/L that we calculated from reported Epeorus latifolium larval survival following 35-d exposures in hardness 83 mg/L water [45]. Ephemerella was also the most sensitive taxa to Cd in the present results, with a 32-d EC50 of approximately 0.37 mg/L in water with a hardness of 17 mg/L (Table 1).…”
Section: Experimental Stream Results Relative To Standard Single-speccontrasting
confidence: 85%
“…These reports demonstrated that parts of macrobenthos were sensitive to zinc. From the view of aquatic organisms protection, Japanese government set environmental water quality standards for zinc to 0.03 mg/L for public freshwater area and 0.02 mg/L for public sea in 2003, based on no observed effect concentration of a mayfly, Epeorus latifolium (Hatakeyama 1989) and 50% inhibitory concentration (IC 50 ) of multiplication of a diatom, Nitzschia closterium (Stauber and Florence 1990). Furthermore, Japanese effluent regulation for zinc was revised from 5 to 2 mg/L in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Because the Japanese Zn standard for freshwater of 30 mg/L was derived from an individual-level laboratory toxicity test (chronic toxicity test with the mayfly Epeorus latifolium [12]), it is uncertain whether the standard is protective, overprotective, or underprotective of populations and communities in natural freshwater environments. Recently, Kamo and Naito [13] focused on the extinction of aquatic populations and estimated, through theoretical population modeling and from the available data from the toxicity tests on various species, that the Zn concentration to achieve 95% species protection was 107 mg/L.…”
Section: Introductionmentioning
confidence: 99%